PENGGUNAAN BLOK DIENES DALAM PEMBELAJARAN PERKALIAN BERSUSUN UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV SDI KUANINO 3 - Janse Dami (Journal of Character and ELementary Education, 2023)
This study aims to improve student learning outcomes in multiplication using the Dienes Block in class IV SDI Kuanino 3, Kupang City. The multiplication multiplication operation is one of the learning materials that is a problem in class IV SDI Kuanino 3 Kupang City; where most of the students have not completed the learning. This causes researchers to improve learning by using the Dienes Block as a problem-solving solution. This research is a Classroom Action Research (planning, implementing, observing, testing, and reflecting). The subjects of this study were 26 grade IV students at SDI Kuanino 3, Kupang City. Collection using test and observation techniques with quantitative descriptive data analysis. The results showed an increase in student learning outcomes by 62% of students completing the first cycle and 89% in the second cycle. Based on these results, it can be concluded that using the Dienes Block can improve student learning outcomes on multiplication in class IV SDI Kuanino 3, Kupang City.